Chemistry of Pyrones, Part 3: New Podands of 4H-Pyran-4-ones - Aziz Shahrisa; Alireza Banaei (Molecules, 2000)
New derivatives of 3,5-disubstituted 4H-Pyran-4-one podands (9-15) were prepared by transesterification reaction of dimethyl or diethyl 2,6-dimethyl-4H-pyran-4-one-3,5-dicarboxylate with some glycol, glycol ethers or by nucleophilic substitution of some phenols or glycol ethers with 3,5-bis (bromomethyl)-2,6-diphenyl-4H-pyran-4-one.